2022
DOI: 10.1177/23998083221108403
|View full text |Cite
|
Sign up to set email alerts
|

Realising the Sustainable Development Goal 11.7 in the post-pandemic era – A case study of Taiwan

Abstract: The COVID-19 pandemic has dramatically impacted our daily lives worldwide. For instance, pandemic-prevention policies restrict people’s mobility, which causes problems in accessing urban greenspaces. Indeed, unequal access to urban greenspace has been accentuated during the most stringent lockdowns of 2020 and 2021. Amid such challenging circumstances, there has been a growing attention placed on Sustainable Development Goal (SDG) 11.7, which has brought opportunities for urgent action. In this paper, we appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…This aligns well with other research that indicated a lack of social distancing and crowded UGSs as a main concern, for instance in New York City [52]. Empirical research in Taiwan showed that two-thirds of the urban planning area suffers from unequal access to UGSs, and this unequal access has been stressed during the lockdowns [53]. A study in Malaysia showed that the size of existing UGSs is insufficient in terms of compliance with the parameters, especially Malaysia's social distancing requirements [54].…”
Section: Available Qualities and Size For A Better Experiencesupporting
confidence: 89%
“…This aligns well with other research that indicated a lack of social distancing and crowded UGSs as a main concern, for instance in New York City [52]. Empirical research in Taiwan showed that two-thirds of the urban planning area suffers from unequal access to UGSs, and this unequal access has been stressed during the lockdowns [53]. A study in Malaysia showed that the size of existing UGSs is insufficient in terms of compliance with the parameters, especially Malaysia's social distancing requirements [54].…”
Section: Available Qualities and Size For A Better Experiencesupporting
confidence: 89%
“…The second surprise was that I could find no reference to the United Nations Sustainable Development Goals (SDGs) despite the fact that SDG11 is focused on urban areas. That said, SDGs are only beginning to be a topic of research in EPB; see, e.g., and Thomas et al (2021) and Hsu et al (2023). However, it does seem to reinforce the disconnect between national monitoring programs and what is happening at the local level, even though implementation of the SDGs requires engagement with local communities and subnational governments in order to be successful.…”
Section: The Innovative Role Of Cities In Solving Global Problems Wit...mentioning
confidence: 99%